What about sex, race(ism), and social determinants of health in neonatal outcomes? - Chaudhary, Neha; Meharwal, Arushi (Frontiers in Pediatrics, 2024)
Neonatal outcomes encompass a range of outcome measures, including mortality rates, physical and mental health morbidities, and long-term neurodevelopmental statistics. These outcomes are influenced by non-modifiable factors, such as sex and race, and modifiable factors, such as social determinants of health and racism. There is a known bias toward worse outcomes for male infants in terms of preterm birth, low birth weight, and mortality, with several biological and physiological factors contributing to these sex-related differences. In relation to racial disparities, wherein race is a social construct, maternal and infant healthcare continues to lag behind for minority populations compared with the white population, despite advances in medical care. Infants born to Black women have higher infant mortality rates and lower birth weights than infants of white women. These differences can be largely attributed to social and environmental factors, rather than racial and ethnic differences. Furthermore, we emphasize the role of social determinants of health in neonatal outcomes. Factors such as economic stability, education access and quality, healthcare access and quality, the physical neighborhood environment, and the social and community context all contribute to these outcomes. Overall, this article highlights the complex interactions between sex, race(ism), and social determinants of health in neonatal outcomes. It underscores the need for a comprehensive understanding of these factors to improve maternal–neonatal care and reduce disparities in outcomes. Healthcare providers, policymakers, and communities need to work together to combat these complex issues and improve neonatal outcomes for all infants, while understanding the complex interplay between sex, racism, and/or social determinants of health.